Тенденции развития рынка молока и молочной продукции Украины - Шквыря, Наталья Александровна; Шквиря, Наталя Олександрівна; Shkvyria, Natalia; Любишко, Д. О. (ИжГТУ имени М.Т. Калашникова, 2015)
RU: В статье проанализировано состояние рынка молока и молочной продукции Украины. Определены основные тенденции и приоритетные направления его развития. Обоснованы возможные пути повышения конкурентоспособности товаропроизводителей на рынке молока и молочной продукции.EN: The article analyzes the condition of the milk and milk products’ market in Ukraine. Key trends and priorities of the market were determined. Possible ways to improve the competitiveness of pro-ducers market in milk and milk products were substantiated.
Market development trends in milk and milk products’ market in Ukraine
Keywords: рынок молока и молочной продукции; конкурентоспособность предприятия; milk and milk products’ market; the competitiveness of enterprise